Surface CD107a/LAMP-1 protects natural killer cells from degranulation-associated damage - Cohnen, André; Chiang, Samuel C.; Stojanovic, Ana; Schmidt, Hendrik; Claus, Maren; Saftig, Paul; Janßen, Ottmar; Cerwenka, Adelheid; Bryceson, Yenan T.; Watzl, Carsten (Blood, 2013)
Cytotoxic lymphocytes are important for immune responses against viral infections and cancer. They are able to kill target cells through the release of cytotoxic granules (CGs) without being harmed in the process. Because the lysosomal-associated membrane proteins (LAMPs) appear on the cell surface after CG exocytosis, we hypothesized that some of these proteins might be involved in transiently protecting cytotoxic lymphocytes from self-destruction. Intracellular expression of CD107a/LAMP-1, and to a lesser extent that of CD107b/LAMP-2, correlated with lymphocyte CG content. Engineered surface expression of CD107a/LAMP-1, but not of CD107b/LAMP-2, reduced the granule-mediated killing of transfected target cells. This was dependent on glycosylation of the CD107a/LAMP-1 hinge. Moreover, surface expression of CD107a/LAMP-1 reduced binding of perforin to cells. Importantly, knockdown of CD107a/LAMP-1 in primary human natural killer (NK) cells and deficiency of CD107a/LAMP-1 in mice resulted in increased NK cell apoptosis upon target cell-induced degranulation. Thus, our data support a novel role of CD107a/LAMP-1 in the protection of NK cells from degranulation-associated suicide, which may represent a general mechanism to transiently limit self-destruction by cytotoxic lymphocytes upon target cell killing.
Gesehen am 29.04.2021